Protein post-translational modification in SARS-CoV-2 and host interaction - Cheng, Nana; Liu, Mingzhu; Li, Wanting; Sun, BingYue; Liu, Dandan; Wang, Guoqing; Shi, Jingwei; Li, Lisha (Frontiers in Immunology, 2023)
SARS-CoV-2 can cause lung diseases, such as pneumonia and acute respiratory distress syndrome, and multi-system dysfunction. Post-translational modifications (PTMs) related to SARS-CoV-2 are conservative and pathogenic, and the common PTMs are glycosylation, phosphorylation, and acylation. The glycosylation of SARS-CoV-2 mainly occurs on spike (S) protein, which mediates the entry of the virus into cells through interaction with angiotensin-converting enzyme 2. SARS-CoV-2 utilizes glycans to cover its epitopes and evade the immune response through glycosylation of S protein. Phosphorylation of SARS-CoV-2 nucleocapsid (N) protein improves its selective binding to viral RNA and promotes viral replication and transcription, thereby increasing the load of the virus in the host. Succinylated N and membrane(M) proteins of SARS-CoV-2 synergistically affect virus particle assembly. N protein regulates its affinity for other proteins and the viral genome through acetylation. The acetylated envelope (E) protein of SARS-CoV-2 interacts with bromodomain-containing protein 2/4 to influence the host immune response. Both palmitoylation and myristoylation sites on S protein can affect the virus infectivity. Papain-like protease is a domain of NSP3 that dysregulates host inflammation by deubiquitination and impinges host IFN-I antiviral immune responses by deISGylation. Ubiquitination of ORF7a inhibits host IFN-α signaling by blocking STAT2 phosphorylation. The methylation of N protein can inhibit the formation of host stress granules and promote the binding of N protein to viral RNA, thereby promoting the production of virus particles. NSP3 macrodomain can reverse the ADP-ribosylation of host proteins, and inhibit the cascade immune response with IFN as the core, thereby promoting the intracellular replication of SARS-CoV-2. On the whole, PTMs have fundamental roles in virus entry, replication, particle assembly, and host immune response. Mutations in various SARS-CoV-2 variants, which lead to changes in PTMs at corresponding sites, cause different biological effects. In this paper, we mainly reviewed the effects of PTMs on SARS-CoV-2 and host cells, whose application is to inform the strategies for inhibiting viral infection and facilitating antiviral treatment and vaccine development for COVID-19.